THEORETICAL-METHODOLOGICAL AND PSYCHOLOGICALPEDAGOGICAL ASPECTS OF PHYSICAL EDUCATION OF DIFFERENT GROUPS OF THE POPULATION - Пішак, Ольга Василівна (Pedagogy and Education Management Review (PEMR), 2021)
The proposed academic paper examines the characteristic theoreticalmethodological and psychological-pedagogical aspects of physical education, namely, the basic concepts, training models, the specifics of the practical implementation of physical education of various groups of the population in today’s conditions. The purpose of the academic paper is to analyze the theoretical and methodological and psychological and pedagogical aspects of physical education of different groups in a modern educational environment. The content of the concepts “physical education” has been investigated by methods of comparative analysis and synthesis; the specifics of physical education of different groups of the population in the conditions of modern educational environment have been characterized; the method of classification of physical education’s methods for different groups of the population has been applied. In order to optimize the existing approaches to physical education of different groups of the population, the process of forming a healthy nation by introducing a social way of life should be considered as the priority task of the state.
Keywords: educational environment, physical education, interactive educational process, healthy nation.